Konseling Motivational Interviewing dan Cognitive Behaviour Dalam Upaya Rehabilitasi Penyalahguna Narkoba Pada Remaja - Nuha, Moch. Syihabudin; Rofiq, Arif Ainur (Universitas Negeri Makassar, 2024)
This study discusses efforts to rehabilitate drug abusers using Motivational Interviewing counseling and Cognitive Behavior Therapy. This research uses qualitative research methods with a case study approach. The research was conducted at the Pratama Clinic of BNN, East Java Province. The subjects in this study were two teenagers with different backgrounds and participated in narcotics counseling at the BNN Pratama Clinic in East Java Province. Data collection was carried out by observation, interviews and providing pre-test and post-test questionnaires. It was shown that before administering the intervention got a score of 11.3 and 11.7. Then after the intervention administration got a score of 12.7 and 12.8, meaning that Motivational Interviewing Counseling and Cognitive Behaviour Therapy can be applied in efforts to rehabilitate drug abusers in adolescents.